Feeding the 10 billion within the sustainable development goals framework - Lautze, Jonathan F.; Noble, A.D. (Routledge, 2016)
Feeding the worlds growing human population is increasingly challenging especially as more people adopt a western diet and lifestyle Doing so without causing damage to nature poses an even greater challenge. This book argues that in order to create a sustainable food supply whilst conserving nature agriculture and nature must be reconnected and approached together.